2019
DOI: 10.3389/fneur.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Cerebellar Signs and Non-motor Features in Chinese Patients With Spinocerebellar Ataxia Type 3

Abstract: Objectives: Our study attempted to systematically explore the prevalence of extra-cerebellar signs and non-motor symptoms, such as anxiety, depression, fatigue, excessive daytime sleepiness (EDS) and sleep disturbances in a cohort of Chinese patients with spinocerebellar ataxia type 3 (SCA3), and further investigated the correlations between non-motor symptoms and clinical characteristics in SCA3 patients. Methods: This study included 68 molecular-proven SCA3 patients. Extra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 42 publications
5
26
0
Order By: Relevance
“…We also found that daytime somnolence and ataxic severity are risk factors associated with fatigue. While daytime somnolence, the length of expanded CAG repeats, anxiety, and depression have been reported to be associated with fatigue (3,19,20,22,23), it was the first time that ataxic severity was found to be associated with fatigue. The significant correlation between fatigue and disease severity was also revealed in a PD cohort (8).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We also found that daytime somnolence and ataxic severity are risk factors associated with fatigue. While daytime somnolence, the length of expanded CAG repeats, anxiety, and depression have been reported to be associated with fatigue (3,19,20,22,23), it was the first time that ataxic severity was found to be associated with fatigue. The significant correlation between fatigue and disease severity was also revealed in a PD cohort (8).…”
Section: Discussionmentioning
confidence: 98%
“…It is clinically characterized by progressive cerebellar ataxia, dysphagia, oculomotor disturbances, and extrapyramidal signs. In addition to the cardinal motor manifestations, SCA3 may also exhibit several non-motor clinical manifestations such as sleep behavior disorders, cognitive deficits, olfactory dysfunction, psychiatric symptoms, nutritional problems, autonomic nervous function disturbances, and fatigue (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Balance impairments in SCA3 are characterised by increased postural sway and poor balance control during both static and dynamic tasks [7] . These impairments are the most frequent initial clinical manifestation in SCA3, which can be quickly recognised by patients as a sign of onset [8] .…”
mentioning
confidence: 99%